Reproductive Biology of Pokea Clams (Batissa violacea var. celebensis, von Martens 1897) at Langkumbe River, Southeast Sulawesi, Indonesia - Bahtiar; Findra, Muhammad Nur; Permatahati, Yustika Intan; Kasim, Ma’ruf (Malaysian Journal of Science (MJS), 2025)
Pokea clams (Batissa violacea) are bivalves that possess different reproductive patterns depending on the location. However, their reproductive pattern in Langkumbe River (Southeast Sulawesi, Indonesia) is unknown. This study aims to determine the sex ratio, gonad maturity level (GML), gonadosomatic index (GSI), fecundity and size of the first gonad maturity of the clams. The samples were collected randomly using iron baskets in all parts of the river and were combined together. The sex ratio, GML, GSI and size at first maturity were calculated using a standard formula, each of which was analyzed using the Chi-Square test, quantitative descriptive analysis as well as simple and non-linear regression. The results showed that the clams were gonochoric with more males than females. Male clams were relatively smaller and ranged from 3.28-3.75 cm in size. Furthermore, gonadal early and late development occurred in February through March and final gonad maturation occurred in April. Gonadal maturation and spawning occurred over a long period from March to October with a pattern of 1 peak spawning marked by an increase in the GSI value in the particular month. The GSI values ​​in males and females were relatively the same, i.e., ​​36.47±16.79 and 34.80±17.71 as well as 18.37±9.46 and 18.57±8.86, respectively. Male pokea clams matured earlier than female with sizes of 1.4 cm or 0.23% and 2 cm or 0.50%, respectively. The reproductive potential of pokea clams in the Langkumbe River is high.